Comparative investigation of phytochemicals among ten citrus herbs by ultra high performance liquid chromatography coupled with electrospray ionization quadrupole time‐of‐flight mass spectrometry and evaluation of their antioxidant properties - He, Ying‐Jie; Zhu, Meng; Zhou, Ying; Zhao, Kang‐Hong; Zhou, Jia‐Li; Qi, Zi‐Heng; Zhu, Yan‐Yan; Wang, Zhao‐Jie; Xie, Tian‐Zhen; Tang, Qi; Wang, Yi‐Fen; Luo, Xiao‐Dong (Journal of separation science, 2020)
The citrus herbs have proved their important medicinal and nutritional values as medicine–food dual‐purpose herbs, functional foods, or medical herbs in China. In this study, phytochemicals and antioxidant activity among ten typical citrus herbs (ethanol extracts) were investigated comprehensively. The major ingredients and their contents were analyzed by high‐resolution mass spectrometry, and the differences of typical fragment ions between flavanone‐7‐O‐rutinoside(s) and flavanone‐7‐O‐neohesperidoside(s) were discriminated properly in negative electrospray ionization mode. Total polyphenols, total flavonoids, 1,1‐diphenyl‐2‐picrylhydrazyl, 2,2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulphonic acid), and ferric reducing antioxidant power tests were performed, which indicated their beneficial values and antioxidant effects. The medicine–food dual‐purpose herbs including Chenpi, Juluo, Daidaihua, Huajuhong, Xiangyuan, and Foshou exhibited antioxidant capacities significantly by decreasing intracellular reactive oxygen species intensity (P < 0.01), enhancing superoxide dismutase, catalase, and glutathione peroxidase activities (P < 0.01) in H2O2‐induced RIN‐m5F cells. Moreover, the functional foods Zhishi, Zhiqiao, and Qingpi showed moderate antioxidant bioactivity, while the medical herb Juhe showed weak antioxidant bioactivity, which were consistent with the multivariate analysis of their major flavonoids. The study provided a new sight for the chemical differentiation and practical application of citrus herbs as medicine–food dual‐purpose herbs, functional foods, or medical herbs.